When Dream Bear Sings : Native Literatures of the Southern Plains - Velie, Alan R., 1937-; Palmer, Gus, 1943- (Book collections on Project MUSE., 2018)
"Collection of songs, orations, myths, stories, legends, and other oral literatures from seven of the major language groups of the Great Plains: Muskogean, Uto-Aztecan, Caddoan, Siouan, Algonquian, Kiowa-Tanoan, and Athabascan"--Provided by publisher.